Representations of excellence in New Zealand micro-enterprise. (22nd January 2007) - Jurado, Tanya; Massey, Claire; Walker, Robyn
This paper reports on a qualitative study on micro-enterprises and firm performance where we adopt a social constructionist approach to analyse responses to the question: 'What does business excellence mean to you?' Most owner-managers found the term to be meaningful, but standard business excellence frameworks were unfamiliar and viewed as irrelevant by some. Our analysis shows excellence for managers of micro-enterprises is a relationship-driven phenomenon represented in terms of personal values, good service, personal satisfaction and positive relationships with clients. Frequently these characterisations are presented against the 'other' of business-in-general. That managers of micro-enterprises construct business excellence differently from accepted models has implications for government policy affecting micro-enterprises. Policy must recognise the special character and diversity of micro-enterprise and attempt to negotiate meaningful interaction that will enable the aspirations of both micro-enterprise and Government to be met.